THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL INCLUSION ON PERFORMANCE OF MICRO, SMALL AND MEDIUM ENTERPRISES IN WEST TOMOHON DISTRICT - Miryam P Lonto; Tesalonika Jeanned Pontoh; Olivia J Lalamentik (ACCOUNTABILITY, 2024)
This study aims to analyze the effect of financial literacy, and financial inclusion on the performance of small and medium on the performance of micro, small and medium enterprises in West Tomohon District. The method used in this research is a quantitative approach with regression analysis, using SPSS 20 software. The sample consisted of 98 respondents selected through a non-probability sampling technique. Based on the results of the t test, financial literacy has a value of significance of 0.039 (smaller than 0.05) and a t value of 2.090 (greater than t table 1.985). The result indicates that financial literacy has a significant influence on the performance of micro, small and medium enterprises. In addition, the t-test for financial inclusion resulted in a significance value of significance of 0.001 (smaller than 0.05) and a t-value of 5.530 (greater than t table 1.985), which indicates that financial inclusion also has a significant effect on the performance of micro, small and medium enterprises. Furthermore, this study found that financial literacy and financial inclusion simultaneously have a significant effect on the performance of micro small and medium enterprise, with a significance value of 0.001 (smaller than 0.05) and an Fcount value of 18.801 (greater than Ftable 3.05).